IT’S REWIND TIME, EVERYBODY: THE CONTESTATION OF PLATFORM CULTURE IN YOUTUBE’S YEARLY REVIEW - Reynolds, CJ (AoIR Selected Papers of Internet Research, 2020)
YouTube Rewind, especially its controversial 2018 and 2019 offerings, surfaces contested and contradictory understandings of what YouTube culture is and who gets to speak for the platform. Adopting and morphing the idea of media events established by Dayan and Katz, I argue that Rewinds serve as social media events. Rewinds are moments of coming together around shared rituals, anthems, and cultural leaders. The violation of the formula for this ceremonial event in 2018 upset audiences and generated a mass, organized, and negative response. By tracing the flows of content creation, including the corporate-produced Rewind videos and critical response and reaction videos from YouTube creators, this project identifies competing visions and structuring tensions of platform culture. Focusing on the question of cultural development on YouTube via the social media event of Rewind videos forefronts the larger question of how researchers can talk about online culture on a globalized scale. From viewer-driven virality, to the establishment of microcelebrities, to the role of international cultural leaders on the platform, understandings of what it means to be a YouTuber emerge from more sectors than ever before. Is a singular Rewind possible for a platform that now encompasses over 100 countries and 80 languages? If corporate visions of what YouTube is and should be no longer generate popular excitement and backing, who then gets to speak for the platform? Focusing on YouTube’s premiere cultural event offers a starting point for understanding what YouTube means to those who structure their lives on and around the platform.